2009
DOI: 10.1007/s12094-009-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral angiogenesis and breast cancer

Abstract: Breast cancer (BC) is the most common neoplasm in women in Western countries. Tumoral angiogenesis (TA) is essential for the growth and spread of BC cells. There are at least 6 different angiogenic growth factors associated with TA in BC. The major mediator of TA is vascular endothelial growth factor (VEGF), a homodimeric heparin-binding glycoprotein. VEGF signals through VEGF receptor-2 (VEGFR-2), the major VEGF signalling receptor that mediates sprouting angiogenesis. Recently, different antiangiogenic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…VEGF has been considered to be a target gene for the estrogen receptors and to contribute to breast cancer progression (Applanat et al, 2008;Khosravi Shahi et al, 2009). Estroegens are known to enhance VEGF expression (Kazi and Koos, 2007) and in breast tumors in vivo, estrogens has been shown to promote angiogenesis and increase extracellular VEGF .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been considered to be a target gene for the estrogen receptors and to contribute to breast cancer progression (Applanat et al, 2008;Khosravi Shahi et al, 2009). Estroegens are known to enhance VEGF expression (Kazi and Koos, 2007) and in breast tumors in vivo, estrogens has been shown to promote angiogenesis and increase extracellular VEGF .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been found to be a target gene for the estrogen receptor and to contribute to breast cancer progression [4,26] . Thus, VEGF could be used as a therapeutic target for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Several preclinical studies have shown that unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) have many anticancer properties that are not dependent on their anticoagulant functions. [27][28][29] Because of the role that platelets play in both hemostasis/thrombosis and cancer, it is reasonable to hypothesize that one mechanism by which anticoagulants affect cancer outcome is by modulating platelet function. The direct effect of anticoagulants on the ability of platelets to regulate angiogenesis and tumorigenesis has not been determined.…”
Section: Introductionmentioning
confidence: 99%